Multiple facets of biodiversity drive the diversity-stability relationship - Craven, Dylan; Eisenhauer, Nico; Pearse, William D; Hautier, Yann; Isbell, Forest; Roscher, Christiane; Bahn, Michael; Beierkuhnlein, Carl; Bönisch, Gerhard; Buchmann, Nina; Byun, Chaeho; Catford, Jane A; et al. (Nature ecology & evolution, 2018)
A substantial body of evidence has demonstrated that biodiversity stabilizes ecosystem functioning over time in grassland ecosystems. However, the relative importance of different facets of biodiversity underlying the diversity-stability relationship remains unclear. Here we use data from 39 grassland biodiversity experiments and structural equation modelling to investigate the roles of species richness, phylogenetic diversity and both the diversity and community-weighted mean of functional traits representing the 'fast-slow' leaf economics spectrum in driving the diversity-stability relationship. We found that high species richness and phylogenetic diversity stabilize biomass production via enhanced asynchrony in the performance of co-occurring species. Contrary to expectations, low phylogenetic diversity enhances ecosystem stability directly, albeit weakly. While the diversity of fast-slow functional traits has a weak effect on ecosystem stability, communities dominated by slow species enhance ecosystem stability by increasing mean biomass production relative to the standard deviation of biomass over time. Our in-depth, integrative assessment of factors influencing the diversity-stability relationship demonstrates a more multicausal relationship than has been previously acknowledged.
Keywords: Grassland; vyšší rostliny; zvláštnosti životní historie; pastviny; Biomass; Life History Traits; biologické modely; Embryophyta; biodiverzita; Models, Biological; fylogeneze; Phylogeny; biomasa; Biodiversity